Fishbein and ajzen's theory of reasoned action with Malaysians' intentions to further studies through virtual education - Foo, Adrian Yoke Pin (1994)
A review of the literature suggested: 1. A greater appreciation of the myriad environments in which learning can take place, in many different settings, inside and outside of the classroom, and at any time. 2. A consensus to be found in purchase intention literature that powerful peer group pressures (or other social influences) can influence and modified the beliefs held by an individual. 3. The success amongst cognitive motivational theories of the Fishbein and Ajzen’s Model of Reasoned Action, a model which explicitly incorporates attitudinal and normative factors. The Fishbein and Ajzen’s Model of Reasoned Action was therefore used as a vehicle to examine hypotheses concerning intention to register as student under a virtual education and to survey a number of beliefs and attitudes towards virtual education. But the principal used of the model was to look for attitudinal and normative influences upon student intentions. The attempt to predict registration intention from attitudinal and normative considerations in line with the Fishbein and Ajzen’s model was largely successful. However, registration intentions of respondents were found not to be influenced by their father. This was quite contrary to expectations. The explanations of this result may lie in the closeness of respondents to their mother than father which is quite common in the Malaysia environment. The study has presented that flexible and convenient were the main advantages of registration under a virtual environment.